MENINGKATKAN KREATIVITAS DAN KEWIRAUSAHAAN ANAK SEJAK DINI DI ISTANA PANTI ASUHAN AL-JUFRI BATAM - Nolla Puspita Dewi; Faris Ramadhan; Mursal Mursal; Liyana Khairunnisa Fawwaz; Liana Liana (Jurnal Abdimas Bina Bangsa, 2024)
The development of the creative economy cannot be separated from the younger generation as a treasure of creativity. A creative idea that can spread entrepreneurship and support the government's efforts in reducing unemployment in Indonesia. This study aims to analyze Increasing Children's Creativity and Entrepreneurship Early at the Palace of Al-Jufri Orphanage Batam. Today's young generation is less able to utilize their productivity and creativity well. There are still many young people who commit crimes from an early age. Therefore, students need to equip them by exploring creative ideas in themselves that can be directed to the business world. Where this young entrepreneur can make the development potential both in number and quality in his own entrepreneur.  With the Community Service Program aimed at the Children of the Orphanage "Al-Jufri Orphan Palace" where this seminar can train independent mentality and creative spirit in entrepreneurship and entrepreneurship.  The results of the study show that with the community service activity program in the form of counseling on Improving Creativity and Entrepreneurship from an Early Age to the children of the orphanage "Al-Jufri Orphan Palace" in Patam Lestari Old Village, Patam Lestari Village, Sekupang District, Batam City, is expected to be able to increase entrepreneurship and entrepreneurship education and provide mental development and creativity of students in entrepreneurship and entrepreneurship and The benefits of entrepreneurship from an early age and can grow an entrepreneurial mentality from an early age